Dubbing Analysis Of Movie Clips And Video Games From English Into Indonesia By Fans - Muhammad Aprianto Budie Nugroho; Erwin Oktoma; Vina Agustiana (Berumpun: International Journal of Social, Politics, and Humanities, 2022)
Dubbing translation research is one of the translation studies in Audio Visual Translation (AVT) that has not been widely discussed, especially with dubbing which is carried out by fans. In this research, the researcher will examine the dubbing done by fans in translating short clips from western films, they are divided into two groups; fundubbing and fandubbing. The fundubing are Fathur Bysmi and Fluxcup, while fandubbing are Raihan Hakim98 and Ky Ameron. Fathur Bysmi dubbed movie clip from Spiderman movie, while Fluxcup dubbed one of Batman TV series entitled Batman the Batus. Raihan Hakim98 dubbed video clip from Resident Evil III game, while Ky Ameron dubbed a video clip from the movie entiled Frozen. Based on findings, it can be seen that the two Fundubbing dubbers are poor in translation quality, because they more focused on having fun and not on meaning. On the other hand the Fandubbing dubbers are better at both of dubbing and translation quality. Both of fundubbing and fandubbing are able to maintain synchronization between the voice and lips, as well as synchronization in gestures or kinetic.